Looking behind the line: privatisation and the reification of work in a Brazilian telecommunications company. (1st July 2009) - Simone Wolff,
Abstract : This paper analyses the results of a case study carried out in the call centre of a public Brazilian telecommunications company. The study focused on the working conditions of operators engaged in telemarketing, an activity that relies on computerised data processing as its main working tool. Information was collected on the perceptions of managers and employees of the informatisation of working procedures and of the new forms of management that were adopted to enable these processes to be handled using the new technologies. The analysis was guided by the hypothesis that the application of Information and Communications Technologies (ICTs) in the context of changed organisational parameters inspired by the so-called 'participative administration' approach, has enabled a new kind of exploitation of living labour to emerge, one that is marked by an expropriation and commodification of workers' knowledge, in its cognitive dimension.